Traceability, Validation and Measurement Uncertainty in Chemistry: Vol. 3 Practical Examples - Hrastelj, Nineta; Bettencourt da Silva, Ricardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents worked examples of five analytical procedures. These practical examples address traceability, validation and measurement uncertainty aspects in a systematic and consistent way, and cover applications in the analysis of water, food, as well as ores and minerals. This concept is based on the experiences of the TrainMiCc program, in which more than 9000 laboratory professionals all over Europe have participated.
Determination of Total Reactive Phosphorus in Natural Water by Molecular Spectrophotometry -- Determination of Concentration of Nitrate in Drinking Water by Chromatography -- Determination of Moisture Content (Water Content) in Edible Oil Using the Volumetric Karl Fischer Method According to ISO 8534:1996 -- Determination of Polyphosphates in Meat Products by Spectrophotometric Method According Laboratory-developed Method -- Determination of Mass Fraction of Tio2 and Fe(Tot) in Ilmenite and Titanium Slag.
Keywords: Analytical chemistry; Environmental monitoring; Materials -- Analysis; Water; Hydrology; Analytical Chemistry; Environmental Monitoring; Characterization and Analytical Technique; Water